Association between different types of childhood trauma and parental bonding with antisocial traits in adulthood: A systematic review. (September 2020) - Schorr, Manuela Teixeira; Tietbohl-Santos, Bárbara; de Oliveira, Lucas Mendes; Terra, Luciana; de Borba Telles, Lisieux Elaine; Hauck, Simone
Abstract: Background: ASPD describes individuals with a pervasive pattern of disregard for the rights of others that begins in childhood and continues into adulthood. The relationship between parental bonding, trauma, and ASPD is well established, however, it remains unclear what types of trauma or which patterns of bonding are more associated with ASPD. Objectives: Review the literature regarding what types of trauma and bonding characteristics were related to antisocial personality traits. Method: Systematic searches of PubMed, Embase, Web of Science, and Scielo for studies about the relationship between antisocial personality traits and the Childhood Trauma Questionnaire (CTQ) and/or the Parental Bonding Instrument (PBI). Results: 357 abstracts were selected, and 18 studies met the inclusion criteria. Regarding CTQ, the most consistent finding was the association between physical abuse and neglect to antisocial traits. Sexual abuse was the variable least related to antisocial traits. Regarding PBI, the most consistent finding was the inverse relationship between maternal and paternal care and antisocial traits. Concerning overprotection, the data is less consistent. Also, there was a considerable heterogenity between studies. Conclusions: The literature little explores how these variables interact with each other. Thus, more studies are important to aidpolitical, educational, and public health programs to create preventive initiatives for ASPD.